The extent of inclusion of the skills of the twenty-first century in the Arabic language book for the sixth grade in Jordan The academic year 2018-2019 is a model - ALSIBIEH, SAAD LWYEN (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to identify the extent to which the 21st century skills were included in the Arabic language book for the sixth grade in Jordan. To achieve this objective, the researcher used the descriptive analytical method using the modified content analysis form by the researcher. (7) areas: - Critical thinking and problem solving - Innovation and creativity - Collaboration and work in the team - Leadership - Understanding multicultural culture - Communication, information and information - Culture of computing and information technology and communication - Profession and self-reliant learning. Study in the book of the Arabic language for the sixth grade the first two chapters and the second academic year 2018/2019, and data analysis was used) Hambleton repetitions and percentages, averages, and the expense of honesty has been applied Hampelton equation. And Alpha Kronbach. The results of Test-Retest showed that the method of retest was applied In the light of the results, the researcher recommended reviewing the content of the Arabic language courses for the basic stage in terms of dealing with the skills of the 21st century, in view of their importance in preparing the learner Capable of coping with the challenges and addressing the problems that may be faced.